European Stroke Organisation (ESO) guidelines on the management of space-occupying brain infarction. (June 2021) - van der Worp, H Bart; Hofmeijer, Jeannette; Jüttler, Eric; Lal, Avtar; Michel, Patrik; Santalucia, Paola; Schönenberger, Silvia; Steiner, Thorsten; Thomalla, Götz
Space-occupying brain oedema is a potentially life-threatening complication in the first days after large hemispheric or cerebellar infarction. Several treatment strategies for this complication are available, but the size and quality of the scientific evidence on which these strategies are based vary considerably. The aim of this Guideline document is to assist physicians in their management decisions when treating patients with space-occupying hemispheric or cerebellar infarction. These Guidelines were developed based on the European Stroke Organisation (ESO) standard operating procedure and followed the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. A working group identified 13 relevant questions, performed systematic reviews and meta-analyses of the literature, assessed the quality of the available evidence, and wrote evidence-based recommendations. An expert consensus statement was provided if not enough evidence was available to provide recommendations based on the GRADE approach. We found high-quality evidence to recommend surgical decompression to reduce the risk of death and to increase the chance of a favourable outcome in adult patients aged up to and including 60 years with space-occupying hemispheric infarction who can be treated within 48 hours of stroke onset, and low-quality evidence to support this treatment in older patients. There is continued uncertainty about the benefit and risks of surgical decompression in patients with space-occupying hemispheric infarction if this is done after the first 48 hours. There is also continued uncertainty about the selection of patients with space-occupying cerebellar infarction for surgical decompression or drainage of cerebrospinal fluid. These Guidelines further provide details on the management of specific subgroups of patients with space-occupying hemispheric infarction, on the value of monitoring of intracranial pressure, and on the benefits and risks of medical treatment options. We encourage new high-quality studies assessing the risks and benefits of different treatment strategies for patients with space-occupying brain infarction.